2005
DOI: 10.1577/t04-070.1
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐Term Residence of Red Snapper on Artificial Reefs in the Northeastern Gulf of Mexico

Abstract: Red snapper Lutjanus campechanus (N ϭ 54) were tagged and tracked on 12 artificial reefs in the northeastern Gulf of Mexico. Fish were surgically implanted with ultrasonic transmitters and monitored with Vemco remote receivers and Sonotronics surface receivers from August 2000 to July 2004. Four fish were manually tracked from the surface overnight, and their positions were recorded every hour for either 9 or 16 h. The total length of fish tagged was 589 Ϯ 14 mm (mean Ϯ SE). The number of detections by the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
72
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 18 publications
17
72
2
Order By: Relevance
“…Although other relationships between detection probability (DP) and distance have been previously used (e.g., linear or near-gaussian; Hobday and Pincok 2011;Melnychuck 2012), there is evidence that this relationship is best described by a logistic regression (Szedlmayer and Schroepfer 2005;Melnychuk and Walters 2010;How and de Lestang 2012). R 3.0.1 (R Development Core Team 2011) was used for data processing and statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although other relationships between detection probability (DP) and distance have been previously used (e.g., linear or near-gaussian; Hobday and Pincok 2011;Melnychuck 2012), there is evidence that this relationship is best described by a logistic regression (Szedlmayer and Schroepfer 2005;Melnychuk and Walters 2010;How and de Lestang 2012). R 3.0.1 (R Development Core Team 2011) was used for data processing and statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Through this opening, we inserted the tag into the peritoneal cavity and closed the incision with Monocryl dissolvable sutures using a cutting needle. Equipment and tags were sterilized with Betadine (Szedlmayer and Schroepfer 2005). To reduce stress during surgery, the gills and external body surface were irrigated at all times with estuary water and the measuring board was kept moist.…”
Section: Methodsmentioning
confidence: 99%
“…Collection of larger juvenile Red Snapper in the fall seems reasonable because the fish had more time to grow, but as mentioned earlier the greater mean TL during fall may have resulted from the movement of larger Red Snapper onto the artificial reefs during our study. Szedlmayer and Schroepfer (2005) found that Red Snapper were resident on artificial reefs for several seasons, and those authors did not detect any seasonal migration away from their study reefs; however, various other studies have shown probable seasonal movements of Red Snapper. Wells (2007) found that seasonal size differences at specific reef habitats were likely a result of seasonal emigration and immigration of different size-groups of Red Snapper.…”
Section: Discussionmentioning
confidence: 69%
“…Watterson et al (1998) and Patterson et al (2001b) found greater dispersal of tagged adult Red Snapper at large during hurricanes, although studies by Szedlmayer and Schroepfer (2005) and Topping and Szedlmayer (2011b) indicated that the extent of hurricane-caused dispersal was related to reef size, with larger reef structures having lower dispersal of fish. Turpin and Bortone (2002) found a greater abundance of larger Red Snapper on study reefs after Hurricane Erin and Hurricane Opal; this result may have been attributable to (1) inshore movement of larger Red Snapper after the disturbances or (2) displacement and mortality of smaller individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation